Functionalized CNTs with DOPO and Silicon Containing Agents: Effective Reinforcer for Thermal and Flame Retardant Properties of Polystyrene Nanocomposites - Qian, Xiaodong; Shi, Congling; Jing, Jingyun; Che, Honglei (Frontiers in Chemistry, 2021)
DOPO and silicon containing agents modified multiwalled carbon nanotubes (MCNTs) were synthesized through sol-gel process and MCNTs are introduced into polystyrene (PS) through in situ polymerization. TEM observations and FTIR results of MCNTs demonstrated that the MCNT nanofillers were coated with the organic/inorganic flame retardant compound. Moreover, the TEM results of the composites indicate that MCNTs dispersed in polystyrene PS matrix uniformly due to the modification. The PS/MCNTs composites showed improved thermal stability as well as flame retardant properties in comparison with PS/CNTs composites, which are due to the good dispersion of MCNT in the PS matrix. MCNTs in the PS matrix can also reduce the peak heat release rate, total heat release and improve the smoke suppression performance. The improved flame retardant properties are attributed to the char reinforcing effect of CNTs, which can provide enough time for MCNTs and organic/inorganic compound to trap the degradation of polymer chains and catalyze the formation of char. The char layers can not only serve as an efficient insulating barrier to reduce the exposure of PS matrix to heat source but also retard the releasing of combustible gas.